Kajian Strategi dan Global : Strategi Keamanan Nasional - Kardi, Koesnadi (UI Scholars Hub, 2018)
National Security Strategy is a vast subject involving a daunting array of interrelated subelements woven in intricate, sometimes vague, and ever-changing patterns. Its processes are often irregular and confusing and always based on difficult decisions laden with serious risks. In short, it is a subject undestood by few and confusing to most. It is, at the same time, a subject of everwhelming important to the fate of civilization itself. Col. Dennis M. Drew and Dr. Donald M have done a considerable service by drawing together many of the diverse threads of national security strategy into a coherent whole. They consider political and military strategy elements as part of a larger decision making process influenced by economic, technological, cutural, and historical factors. We know of no other recent volume that addresses the entire nationalm security milieu in such a logical manner and yet also manages to address current concerns so thoroughly. It is equally remarkable that they have addressed so many contentious problems in such an evenhanded manner. We are convinced that experienced practitioners in ther field of national security strategy would benefit greatly from a closed examination of this excellent book.